Analisis Hubungan Hardiness dan Career Adaptability pada Generasi Z yang Bekerja sebagai Content Creator di Indonesia - Reininda Anugrah Hayati; Rayini Dahesihsari (Humanitas (Jurnal Psikologi), 2025)
For today's Generation Z, career exploration is not just a developmental phase but also an adaptive process in responding to dynamic career challenges caused by technological disruption, social changes, and the impact of the pandemic. The gig economy has emerged as an alternative for Generation Z who find it difficult to access formal employment, but it also brings uncertainty in terms of income and employment status. Therefore, career adaptability is important for Generation Z who work as content creators. This descriptive-correlational quantitative study aims to analyze the relationship between hardiness and career adaptability among Generation Z who work as content creators. The study employed convenience sampling and obtained 331 participants who met the criteria for completing the DRS-II scale, the CAAS scale, and open-ended questions in the questionnaire. Since the data are not normally distributed, Spearman's rank correlation was used to test the correlation between the two variables. The results showed a significant positive relationship between hardiness levels and career adaptability. This means that the higher the level of hardiness, the higher the level of career adaptability among Generation Z working as content creators. The main implications of the research findings is that hardiness is essential to remain relevant and in demand in pursuing a career as a content creator. The education sector, communities, and relevant government institutions can offer programs to develop hardiness in support of content creators' career development.